1981
DOI: 10.1159/000123133
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Function in the Empty Sella Syndrome

Abstract: The empty sella syndrome is defined as an intrasellar cisternal herniation in combination with a deformed and/or enlarged sella turcica, but without clinical signs of a pituitary adenoma. In the present study, the impact of the cisternal herniation on pituitary function was analyzed. Special emphasis was placed on the relationship between pituitary function and the size and shape of the sella and type of herniation. The diagnosis of the empty sella syndrome was verified by pneumoencephalography in 49 out of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…Rogol et al (1985) reported that empty sella was found in their familial pituitary dwarfs, although they had multiple deficiencies of anterior pituitary hormones. It is well known that endocrine dysfunctions were detected in only 10-20% of empty sellas, but secretion failurse of Gil were found most commonly in patients with empty sellas (Brismer and Efendic 1981). The present findings together with these reports also led us to consider that lesion of our IGHD was pituitary.…”
Section: Discussionsupporting
confidence: 78%
“…Rogol et al (1985) reported that empty sella was found in their familial pituitary dwarfs, although they had multiple deficiencies of anterior pituitary hormones. It is well known that endocrine dysfunctions were detected in only 10-20% of empty sellas, but secretion failurse of Gil were found most commonly in patients with empty sellas (Brismer and Efendic 1981). The present findings together with these reports also led us to consider that lesion of our IGHD was pituitary.…”
Section: Discussionsupporting
confidence: 78%
“…Empty sella is a frequent finding in imaging studies (36,37), but it should be kept in mind that SS is a rare cause of empty sella. Brismar & Efendic (38) found that SS was present in only one out of 50 patients with empty sella and Jara-Albarran et al (39) diagnosed SS in none of the 41 patients with empty sella.…”
Section: Discussionmentioning
confidence: 99%
“…This was presumably due to a primary loss of pituitary volume similar to the secondary loss reported in patients with post partum pituitary necrosis or Sheehan's syndrome [27,28],…”
Section: Discussionmentioning
confidence: 63%